Benefits of nostalgia in vulnerable populations. Issue 1 (2nd January 2023) - Wildschut, Tim; Sedikides, Constantine
ABSTRACT: The COVID-19 pandemic has triggered and exacerbated psychological distress, and exposed psychological vulnerabilities, in large swathes of the population. Under challenging circumstances, nostalgia may convey tangible psychological and physical health benefits. We review recent evidence for nostalgia's utility in vulnerable populations, including sojourners and immigrants, civil war refugees, people suffering bereavement, people facing a limited time horizon, and people living with dementia. Having raised the prospect of a positive role for nostalgia in responding to adversity, we next present findings from a series of randomised nostalgia interventions and their impact over time in the workplace, during the COVID-19 pandemic, and at university, respectively. We conclude by offering evidence-based recommendations for future interventions, highlighting the importance of optimal person-activity fit, diversity of content, and accessibility of delivery mechanisms.